Effect of aromatic substitution on the cure reaction and network properties of anhydride cured triphenyl ether tetraglycidyl epoxy resins. (26th March 2019) - Varley, Russell J.; Dao, Buu; Nguyen, Tri; Lee, Sunglin; Nishino, Takashi
Abstract : A systemic study of the impact of aromatic substitution on the reaction rate and network properties of the isomers of a tetraglycidylaniline triphenyl ether epoxy resin cured with anhydride hardeners is presented here. The epoxy resins synthesized in this work were based upon N, N, N, N ‐tetraglycidyl bis(aminophenoxy)benzene (TGAPB), where the glycidyl aniline and ether groups change from being all meta (133 TGAPB), to meta and para (134 TGAPB), and finally to an all para substituted epoxy resin (144 TGAPB). Increasing para substitution increased reaction rate, promoted the onset of vitrification and increased epoxide conversion. Thermal properties such as glass transition temperatures (Tg ) and coefficients of thermal expansion (CTE) both increased consistently with increasing para substitution, although thermal stability as measured via thermogravimetric analysis decreased. Mechanical properties also varied systematically with flexural strength and ductility increasing with increased para substitution, while the modulus decreased. Indeed, the ductility almost doubled, as measured by the work of fracture and displacement at failure highlighting the importance of substitution on properties.